Slime mould games based on rough set theory - Pancerz, Krzysztof; Schumann, Andrew (Zielona Góra: Uniwersytet Zielonogórski)
We define games on the medium of plasmodia of slime mould, unicellular organisms that look like giant amoebae. The plasmodia try to occupy all the food pieces they can detect. Thus, two different plasmodia can compete with each other. In particular, we consider game-theoretically how plasmodia of "Physarum polycephalum and Badhamia utricularis" fight for food. Placing food pieces at different locations determines the behavior of plasmodia.
Keywords: slime mould games; "Physarum" machines; transition systems; rough set theory; simulation software